Necessidades formativas dos professores do ensino fundamental II quanto à inclusão escolar dos alunos público-alvo da educação especial (PAEE) - Miranda, Luciane Helena Mendes de (2020)
This research had as general objective to investigate the formative needs of the teachers of Elementary School II, in relation to the pedagogical practices directed to the students with disabilities and, based on this information, to elaborate a training program directed to the formative needs. For an inclusive school, the educational system was and continues to be challenged, corroborating that transformations in thinking and teaching are necessary for everyone involved in the school environment; it is a qualitative research carried out at DE Mogi das Cruzes that includes the cities of Biritiba Mirim, Mogi das Cruzes and Salesópolis; a large school was chosen from each of the three cities in question. 31 teachers of elementary school II were interviewed and the data were analyzed with the theoretical support of the studies of: Ainscow (1995; 2001), Arnaiz Sánchez (2002; 2012), Dorziat (2011; 2013) and Mendes (2015; 2017), on teacher training for special and inclusive education; Gatti (2013a, 2016), Imbernón (2016), Libâneo (2004; 2012), Passos (2016) and Placco and Souza (2002,2006; 2009), regarding teacher education; Sousa and Placco (2016), about the set of dimensions of training; André (2016) and Franco (2015), regarding pedagogical practices; and, finally, Ainscow (1995; 2001) and Arnaiz Sánchez (2000; 2012), regarding inclusive practices. For data analysis, some content analysis procedures were used (BARDIN, 1977). The data were grouped into the following categories: 1. Teachers’ working conditions; 2. Affections and bonds; 3. Difficulties experienced; 4. Teacher development and 5. pedagogical practices. In view of the training needs raised, we developed a training program emphasizing practical actions, aimed at the school inclusion of PAEE students, focused on the teacher's work context and paying attention to organizational culture. For the proposed action, we verified the importance of participation active teacher; the need to sensitize teachers so that they get rid of the idea of the ideal student and work with the real student; to value the idea of working with collaborative groups and that all activities developed during the process are support for teachers to devise new pedagogical practices; in the training proposal suggested here, as in all initial and continued training, bring the set of dimensions organized by Placco (2006, 2008) and we propose the dimension for diversity that aims to consider all students belonging to the current school, as a participative member in the search for knowledge